Vanuatu : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Vanuatu. (IMF Staff Country Reports; Country Report, 2019)
Four years after Cyclone Pam struck Vanuatu causing extensive damages, reconstruction is near completion with full recovery in sight. The authorities are now focused on implementing their broader development plans that were slowed by the rebuilding process, which will require fiscal discipline and reforms to maintain debt sustainability. The authorities should continue their constructive engagement with development partners for technical assistance, capacity development, and concessional and grant-based funding. In parallel continuing to reform and strengthen the governance of institutions and removing vulnerabilities to corruption will be important.